Does nonmetastatic inflammatory breast cancer have a worse prognosis than other nonmetastatic T4 cancers?. Issue 22 (11th October 2018) - Romanoff, Anya; Zabor, Emily C.; Petruolo, Oriana; Stempel, Michelle; El‐Tamer, Mahmoud; Morrow, Monica; Barrio, Andrea V.
Abstract: Background: Both patients with inflammatory breast cancer (IFLBC) and patients with noninflammatory T4 breast cancer (non‐IFLBC) have a heavy disease burden in the breast; whether the unique biology of IFLBC conveys a higher locoregional recurrence (LRR) risk and worse outcomes in comparison with other T4 lesions is uncertain. Here the outcomes of patients with IFLBC and patients with non‐IFLBC treated with modern multimodality therapy are compared. Methods: Patients with nonmetastatic T4 breast cancer treated with neoadjuvant chemotherapy, mastectomy, and radiation therapy between 2006 and 2016 were identified. Recurrences and survival were compared between patients with IFLBC and patients with non‐IFLBC overall and stratified by receptor subtype. Results: For 199 T4 patients, the median age was 52 years, and the median clinical tumor size was 7 cm. One hundred seventeen (59%) had IFLBC. With a median follow‐up of 41 months, 4 patients had isolated LRR; all cases occurred in patients with IFLBC. The 5‐year isolated LRR rate for patients with IFLBC was 4.8%. Overall, 14 patients had both LRR and distant recurrence (DR); 47 had DR only. The 5‐year distant recurrence–free survival (DRFS) rates were similar for patients with IFLBC and patients with non‐IFLBC (63% vs 71%; log‐rank P = .14). The 5‐year DRFS rate was lowest among triple‐negative (TN) patients (43%) and was significantly lower for patients with TN IFLBC versus patients with non‐IFLBC (28% vs 62%; log‐rank P = .02). The 5‐year overall survival rates (71% vs 74%; log‐rank P = .4) and cancer‐specific survival rates (74% vs 79%; log‐rank P = .23) did not differ between IFLBC and non‐IFLBC. Conclusions: Although IFLBC is often considered a unique biologic subtype, patients with IFLBC and patients with non‐IFLBC had similar outcomes with modern multimodality therapy; isolated LRR was uncommon. The TN subtype in patients with IFLBC is associated with poor outcomes, and this indicates the need for new treatment approaches in this group. Abstract : Patients with inflammatory and noninflammatory breast cancer have similar outcomes with modern multimodality therapy. The triple‐negative subtype in patients with inflammatory breast cancer is associated with poor outcomes, and this indicates the need for new treatment approaches in this group.